The Benefits of Computer Conferences in Distance Education: An Assessment - Gbenga Michael Adeyeye (Noyam Journals, 2024)
This study examined the positive influence of computer conferencing on distance education, particularly its capacity to foster a sense of community, collaboration, and interaction among learners. The study employed semi-structured interviews, focus groups, observations, and document analysis to investigate the experiences of students, instructors, and educational technologists of Delar college of education through a qualitative research design. The primary findings indicated that asynchronous communication provides convenience and flexibility, whereas synchronous communication enables immediate engagement and dynamic discussions. Additionally, computer conferencing facilitates the interchange of information at a rapid pace, reduces feelings of isolation, and facilitates the development of diverse learning environments by facilitating detailed discussions through sub-conferences. The research identified substantial advantages of computer conferencing, but it also emphasized potential constraints, including the necessity for effective facilitation and technological dependence. The research emphasizes the transformative potential of computer conferencing in improving the distance education experience.